Inhibition of tumor-cell-mediated extracellular matrix destruction by a fibroblast proteinase inhibitor, protease nexin I. - Bergman, B L (1986)
Human fibrosarcoma (HT-1080) cells, in contrast to normal fibroblasts, rapidly hydrolyze the glycoprotein, collagen, and elastin extracellular matrix (ECM) synthesized by cultured rat aortic smooth muscle cells. This degradation occurs at a rapid rate in the presence of serum, indicating that the cellular proteases responsible are relatively insensitive to serum proteinase inhibitors. Here it is shown that protease nexin I (PNI), a fibroblast-secreted inhibitor of urokinase, plasmin, and certain other serine proteinases, effectively inhibited the HT-1080 cell-mediated degradation of this ECM. PNI at 2.0 nM significantly inhibited matrix destruction for 1-2 days and at 0.2 microM caused a virtually complete inhibition that persisted for the entire 10-day period of observation. Inhibition of ECM destruction was accompanied by a transient arrest of HT-1080 cell proliferation that took place during the first 3 days after PNI addition. PNI did not inhibit the growth of normal fibroblasts and also did not inhibit the growth of HT-1080 cells that were seeded onto plastic dishes rather than onto ECM. Like many types of malignant cells, HT-1080 cells release large amounts of urokinase. Antibody against this plasminogen activator partially protected ECM from HT-1080 cell-mediated hydrolysis, indicating that it may have been a target of PNI. One potential physiological function of PNI could be to help maintain the integrity of connective tissue matrices, protection that malignant cells could overcome by secreting proteinases in excessive amounts.